2007
DOI: 10.1128/jcm.02188-06
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococcus faecalis Endocarditis: Linezolid Failure and Strain Characterization of Virulence Factors

Abstract: Infective endocarditis due to vancomycin-resistant (VR) Enterococcus faecalis has only rarely been reported. We report a case of VR E. faecalis endocarditis that failed to respond to linezolid therapy, outline the virulence traits of the isolate, and review previously published cases of VR E. faecalis endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…206 On the basis of these susceptibility data, a fluoroquinolone (ciprofloxacin, levofloxacin, or moxifloxacin) may be considered as an alternative agent in patients unable to tolerate ceftriaxone (or other third-or fourth-generation cephalosporins) therapy. There are only a few case reports of HACEK IE treated with a fluoroquinolone, however.…”
Section: Hacek Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…206 On the basis of these susceptibility data, a fluoroquinolone (ciprofloxacin, levofloxacin, or moxifloxacin) may be considered as an alternative agent in patients unable to tolerate ceftriaxone (or other third-or fourth-generation cephalosporins) therapy. There are only a few case reports of HACEK IE treated with a fluoroquinolone, however.…”
Section: Hacek Microorganismsmentioning
confidence: 99%
“…However, linezolid treatment failures of E faecium IE also were reported. 206 The advantages of linezolid therapy include high bioavailability of the oral formulation, approval for pediatric patients, and a lack of many therapeutic alternatives. The disadvantages are toxicity (mild to severe neutropenia and thrombocytopenia that is reversible); peripheral and optic neuritis, which is more often seen with longer durations of therapy and may not be reversible; multidrug interactions, especially serotonin uptake inhibitors; and emergence of resistance during treatment.…”
Section: Linezolidmentioning
confidence: 99%
“…Moreover, we determined high-resolution crystal structures of the best inhibitors in complex with cholix toxin to reveal important criteria for inhibitor binding and mechanism of action. These results provide new insight into development of antivirulence compounds for treating many bacterial diseases.Bacteria use virulence factors as tools to facilitate disease in plants, animals, and humans (14,26,30,34); one strategy to combat infection is to inhibit these factors by small-molecule therapy, thereby helping to neutralize the offending microbe (5,6,12,19,22). It is now generally appreciated that an antivirulence approach is a powerful alternative strategy for antibacterial treatment and vaccine development (27) and that it may require multiple tactics to resolve the current drug resistance dilemma (6,8).…”
mentioning
confidence: 99%
“…However, linezolid showed excellent activity in vitro against E. faecalis and for this high diffusion in tissue it could be used in IE therapy, even if its activity is bacteriostatic. Berdal and Eskesen [30] and Tsigrelis et al [31] have reported failures in the treatment of enterococcal endocarditis with this drug.…”
Section: Discussionmentioning
confidence: 99%